English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

f(x) = 7x + 3

g(x) = (sq. rt.) x

2007-01-08 10:45:58 · 4 answers · asked by Pretty_baby 1 in Science & Mathematics Mathematics

4 answers

adilmaster liked my answer so much that he copied it.

f(x) = 7x + 3
g(x) = √x

(f o g)(x) means to take f(x) and everywhere you see an x, replace it with √x (which is g(x)). This is like "plugging g into f".

(f o g)(x) = f(g(x)) = 7(√x) + 3

(g o f)(x) means to take g(x) and everywhere you see an x, replace it with 7x + 3 (which is f(x)). This is like "plugging f into g".

(g o f)(x) = g(f(x)) = √(7x + 3)

2007-01-08 10:55:22 · answer #1 · answered by Jim Burnell 6 · 1 0

(f o g)(x)= f(g(x))=f((sq.rt.)x) =
7((sq.rt)(x))+3<======= your answer.

(g o f)(x)= g(f(x)) = (sq.rt)(7x+3)


f(x) = 7x + 3
g(x) = √x

(f o g)(x) means to take f(x) and everywhere you see an x, replace it with √x (which is g(x)). This is like "plugging g into f".

(f o g)(x) = f(g(x)) = 7(√x) + 3

(g o f)(x) means to take g(x) and everywhere you see an x, replace it with 7x + 3 (which is f(x)). This is like "plugging f into g".

(g o f)(x) = √(7x + 3)

2007-01-08 10:58:02 · answer #2 · answered by Carpe Diem (Seize The Day) 6 · 0 2

fog(x) = 7(sqrroot(x)) +3
gof(x) = sqrroot(7x+3)

2007-01-08 10:58:22 · answer #3 · answered by akinustun67 1 · 0 0

(f o g)(x) = f(g(x))
f(g(x)) = f(sqrt(x)) = 7sqrt(x) + 3
(f o g)(x) = 7sqrt(x) + 3

(g o f)(x) = g(f(x))
g(f(x)) = g(7x + 3) = sqrt(7x + 3)
(g o f)(x) = sqrt(7x + 3)

2007-01-08 11:48:52 · answer #4 · answered by Sherman81 6 · 0 0

fedest.com, questions and answers